Reconstructed human skin shows epidermal invagination towards integrated neopapillae indicating early hair follicle formation in vitro. (3rd May 2020) - Vahav, Irit; van den Broek, Lenie J.; Thon, Maria; Monsuur, Hanneke N.; Spiekstra, Sander W.; Atac, Beren; Scheper, Rik J.; Lauster, Roland; Lindner, Gerd; Marx, Uwe; Gibbs, Susan
Abstract: Application of reconstructed human Skin (RhS) is a promising approach for the treatment of extensive wounds and for drug efficacy and safety testing. However, incorporating appendages, such as hair follicles, into RhS still remains a challenge. The hair follicle plays a critical role in thermal regulation, dispersion of sweat and sebum, sensory and tactile functions, skin regeneration, and repigmentation. The aim of this study was to determine whether human neopapilla could be incorporated into RhS (differentiated epidermis on fibroblast and endothelial cell populated dermis) and whether the neopapillae maintain their inductive follicular properties in vitro. Neopapillae spheroids, constructed from expanded and self‐aggregating dermal papilla cells, synthesized extracellular matrix typically found in follicular papillae. Compared with dermal fibroblasts, neopapillae showed increased expression of multiple genes (Wnt5a, Wnt10b, and LEF1) known to regulate hair development and also increased secretion of CXCL1, which is a strong keratinocyte chemoattractant. When neopapillae were incorporated into the dermis of RhS, they stimulated epidermal down‐growth resulting in engulfment of the neopapillae sphere. Similar to the native hair follicle, the differentiated invaginating epidermis inner side was keratin 10 positive and the undifferentiated outer side keratin 10 negative. The outer side was keratin 15 positive confirming the undifferentiated nature of these keratinocytes aligning a newly formed collagen IV, laminin V positive basement membrane within the hydrogel. In conclusion, we describe a RhS model containing neopapillae with hair follicle‐inductive properties. Importantly, epidermal invagination occurred to engulf the neopapillae, thus demonstrating in vitro the first steps towards hair follicle morphogenesis in RhS.